2022
DOI: 10.13057/biodiv/d230911
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance pattern of Extended-Spectrum ?-Lactamase (ESBL) producing Escherichia coli isolated from broiler farm environment in Pasuruan district, Indonesia

Abstract: Abstract. Yanestria SM, Dameanti FNAEP, Musayannah BG, Pratama JWA, Witaningrum AM, Effendi MH, Ugbo EN. 2022. Antibiotic resistance pattern of Extended-Spectrum ?-Lactamase (ESBL) producing Escherichia coli isolated from broiler farm environment in Pasuruan district, Indonesia. Biodiversitas 23: 4460-4465. Escherichia coli is one of the bacteria that can be used as an indicator of environmental pollution. This bacterium has the ability to become an antimicrobial-resistant bacterium that impacts public health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…According to a study conducted by Lukman et al [31], ESBL-producing E. coli was present in broiler feces in Bogor, Indonesia, which was related to the findings in this study. The results of this study are in accordance with several studies in Indonesia which reported that the ESBL-producing E. coli were identified from feces of broilers in Bogor reached 25% [32]; cloacal swabs of broilers from wet markets in Surabaya [23]; cloacal swab of layers in Blitar reached 7.03% [28]; swab cages and wastewater around broiler farm in Pasuruan 9.14% [33]; samples of chicken meat sold at Purwokerto's market reached 7.14% [34]; from environmental samples of dairy farms in Yogyakarta, Probolinggo, and East Java [35][36][37]; and from companion dogs in Surabaya reached 9.41% [38]. These findings were also similar to those reported by Lemlem et al [24], who detected blaCTX-M and blaTEM from broilers in Malaysia.…”
Section: Sample Code Esbl Gene Blatem Blactx-m Blashvsupporting
confidence: 91%
“…According to a study conducted by Lukman et al [31], ESBL-producing E. coli was present in broiler feces in Bogor, Indonesia, which was related to the findings in this study. The results of this study are in accordance with several studies in Indonesia which reported that the ESBL-producing E. coli were identified from feces of broilers in Bogor reached 25% [32]; cloacal swabs of broilers from wet markets in Surabaya [23]; cloacal swab of layers in Blitar reached 7.03% [28]; swab cages and wastewater around broiler farm in Pasuruan 9.14% [33]; samples of chicken meat sold at Purwokerto's market reached 7.14% [34]; from environmental samples of dairy farms in Yogyakarta, Probolinggo, and East Java [35][36][37]; and from companion dogs in Surabaya reached 9.41% [38]. These findings were also similar to those reported by Lemlem et al [24], who detected blaCTX-M and blaTEM from broilers in Malaysia.…”
Section: Sample Code Esbl Gene Blatem Blactx-m Blashvsupporting
confidence: 91%
“…Antimicrobial resistance in bacteria can be generated by antibiotic overuse by humans, antibiotic use in animal feed or veterinary treatment, and increased industrial waste in the environment [ 26 , 32 , 42 ]. Bacterial resistance to antimicrobials has evolved in a variety of ways; in most situations, bacteria exposed to antibiotics discover ways to avoid or resist antimicrobial agents [ 31 , 40 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of E. coli in wastewater, especially strain enteropathogenic and toxigenic properties, cause gastrointestinal disorders in public health problems (Jang et al 2017). In other research by Yanestria et al (2022) on wastewater from broiler farm environments were 41 samples (64.62%) positive E. coli isolates and 24 samples (36.92%) positive E. coli with the ability resistant to 3 more antibiotics. Support research on several samples from dairy farm environments by Maulana et al (2020) identified 127 samples (22.75%) of positive E. coli isolates, including 15 (16%) from 93 wastewater samples that were resistant to 3 more antibiotics.…”
Section: Discussionmentioning
confidence: 97%